2014
DOI: 10.1063/1.4890852
|View full text |Cite
|
Sign up to set email alerts
|

Highly focused and efficient terahertz radiation generation by photo-mixing of lasers in plasma in the presence of magnetic field

Abstract: A mechanism of efficient and highly focused terahertz (THz) radiation generation by photo-mixing of top-hat like lasers with frequencies ω1, ω2 and wave numbers k1, k2 in pre-formed rippled density (corrugated) plasma is proposed. In this mechanism, intensity variation of lasers offers nonlinear ponderomotive force at frequency ω′=ω1−ω2 and wave number k′=k1−k2 which couples with density ripples in the plasma and leads to a strong nonlinear oscillatory current that resonantly excites highly focused and intense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Kumar et al [68] studied Beat excitation of terahertz radiation from two different frequency infrared lasers of TM/TE mode propagating along z direction in a rippled density semiconductor waveguide slab in a magnetic field (applied transvers to it) and the terahertz yield is significantly higher in the TM mode laser beating than in the TE mode laser beating. Malik and Malik [69][70][71][72] investigated the role of an external DC magnetic field in tuning the frequency and power of terahertz radiation. Varshney et al [73,74] proposed a scheme for the generation of THz radiation from rippled density magnetized plasma by beating of extraordinary mode lasers.…”
Section: Beat Wave Schemesmentioning
confidence: 99%
“…Kumar et al [68] studied Beat excitation of terahertz radiation from two different frequency infrared lasers of TM/TE mode propagating along z direction in a rippled density semiconductor waveguide slab in a magnetic field (applied transvers to it) and the terahertz yield is significantly higher in the TM mode laser beating than in the TE mode laser beating. Malik and Malik [69][70][71][72] investigated the role of an external DC magnetic field in tuning the frequency and power of terahertz radiation. Varshney et al [73,74] proposed a scheme for the generation of THz radiation from rippled density magnetized plasma by beating of extraordinary mode lasers.…”
Section: Beat Wave Schemesmentioning
confidence: 99%
“…Utilizing the method in refs [30,31,38,[65][66][67] , the efficiency of the emitted radiation, which is the ratio of the energy of THz radiation to the energy of the incident lasers, can be derived as: eff = (Equation 1 and 2), and f ′ (y) = df (y)/dy. For the definition of G, G 1 , G 2 , G 3 , G 4 , refer to Appendix B.…”
Section: Derivation Of Thz Radiation Field and Efficiencymentioning
confidence: 99%
“…[39] The other routes for THz radiation generation include transition radiation from electron beams, [40,41] gyrotrons, [42,43] plasma wakefield, [44] free electron lasers, [45,46] Schottky diodes, [47] and heterojunction barrier varactors. [65] Singh et al have reported THz generation by mixing two cosh-Gaussian laser beams in a density rippled plasma. [54,55] Solid-state electronic sources include the Gunn diode [56,57] and high-frequency transistors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of an external magnetic field perpendicular to the direction of laser pulse propagation could increase the radiation efficiency up to several times more than the absence of a magnetic field. [21][22][23][24][25][26] Since the resonance excitation depends on the tuning of pulse frequency and plasma density, the different types of plasma density, for example, the ripple density, is used to increase the terahertz radiation efficiency. [27][28][29] The terahertz generation by the beating of two Gaussian laser beams for periodically modulated density in the presence of a static magnetic field has been studied by Malik et al [14] Their analytical calculations show that the resonant excitation of THz under the mentioned conditions is quite effective.…”
Section: Introductionmentioning
confidence: 99%